Transient Hypophosphatemia as Possible Adverse Outcome after Iron Deficiency Anemia Treatment with Ferric Carboxymaltose – Single Center Experience - Nikolina Brkić; Ivana Vučinić Ljubičić; Hrvoje Holik; Božena Coha (Acta Clinica Croatica, 2024)
The aim of this study was to determine the frequency of hypophosphatemia in female patients with iron deficiency anemia (IDA) treated parenterally with ferric carboxymaltose (FCM). Thirty-two female patients examined for IDA at the Hematology and Oncology Department of one General Hospital were included in the study. The inclusion criteria were hemoglobin <110 g/L, transferrin saturation <50%, ferritin <30 ng/mL, and ineffective oral iron therapy. The hemoglobin values were significantly increased 6 weeks after therapy in comparison with initial values. The onset of the asymptomatic hypophosphatemia was observed in 17 of 32 patients two weeks after the FCM therapy. Only one of 32 patients had severe asymptomatic hypophosphatemia (serum phosphate <0.3 mmol/L). Prolonged hypophosphatemia (6 weeks after FCM therapy) was observed in five of 32 patients, of which only one patient had initial hypophosphatemia. The difference between the phosphate values measured two weeks after the FCM therapy and the phosphate values at the first and last follow-up was statistically significant. Serum phosphate values should be routinely measured before and after parenteral FCM therapy.